Model Make A Match Berbantu Media Kartu Q&A (Question and Answers) Terhadap Kemampuan Memahami Materi Dongeng - Gita Kurnia Dewi; Dingding Haerudin (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the effect of the make a match model assisted by question and answers card media on the ability to understand fairy tale material in class X students of SMAN 10 Garut. The subjects of this research were students in class X-3 as the experimental class and class X-11 as the control class. Data collection techniques in this study used tests and observations. Testing the data in this study used a true experimental design with the pretest-posttest control group type. The results showed that the t test in the experimental group and the control group was tcount ttable (17.708 1.995), so that a decision could be made that H0 was rejected. This shows that there is an influence of the make a match model assisted by question and answers card media on the ability to understand fairy tale material in class X students of SMAN 10 Garut.